Pengaruh Iklan Jd.Id di Youtube Terhadap Minat Untuk Menggunakan Aplikasi - Wangi Pradana Pandu Briyan Afgani; Muhammad Ramdhani; Flori Mardiani Lubis (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
The purpose of this study was to determine the effect of using Youtube Ads on interest in using the Jd.id application where the variables used include intensity, message content, and attractiveness. The method used is quantitative with a multiple linear regression approach. The target population is employees of the H.R Operations Department of Perum Peruri Karawang with a total of 63 people. The results showed that the variable intensity, message content, and attractiveness of Youtube ads simultaneously had a significant effect on the interest in using the Jd.id application with a total influence of 67.1%. After testing the coefficient of partial determination, the effect of the intensity is 14.1%, the message content is 6.6% and the attractiveness is 36.4%.